(untitled) (International Journal of Social Research & Innovation, 2023)
The objective of the action research study presented in this paper was to teach postgraduate students the soft skills they find valuable and believe are challenging for them to learn, and to gain knowledge of their learning experience. Convenience sampling was used to recruit fifteen Master of Science in Accounting and Finance (MScAFM) students, who voluntarily enrolled in a stand-alone, soft skills education module offered to them, which was delivered through collaborative learning and case method. The learning approaches and content were designed based on a pre-assessment task where students identified their existing knowledge and learning needs. Data was collected using a survey questionnaire, field observations and semi structured interviews. The findings show that the students in this study most highly valued leadership skills, time management, and communication skills and believed that having these traits will make it easier for them to achieve their goals in both their professional and personal lives. Students found it difficult to use critical thinking skills, and to work collaboratively. They are also unable to transfer their knowledge and skills effectively in work-related situations. Hence, soft skill qualities, such as creativity, adaptability, and collaboration should be developed as part of educational activities that strongly emphasize their practical application in different contexts. Engaging in this action research project gave the students the confidence to have a voice, as was described by the students. Students’ voluntary completion rates for the module indicate the high value students place on gaining soft skills.